2020
DOI: 10.1038/s41467-020-18678-0
|View full text |Cite
|
Sign up to set email alerts
|

Viral gene drive in herpesviruses

Abstract: Gene drives are genetic modifications designed to propagate in a population with high efficiency. Current gene drive strategies rely on sexual reproduction and are thought to be restricted to sexual organisms. Here, we report on a gene drive system that allows the spread of an engineered trait in populations of DNA viruses and, in particular, herpesviruses. We describe the successful transmission of a gene drive sequence between distinct strains of human cytomegalovirus (human herpesvirus 5) and show that gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 59 publications
3
36
0
Order By: Relevance
“…We first attempted to model the evolution of gene drive resistance using numerical simulations. Our initial study indicated that after co-infection with a wildtype and a gene drive viruses, around 5-10% of viruses remained unconverted and had a mutated target site that rendered them resistant to the drive (7). Using a 10% estimate and considering in this scenario that resistant viruses would replicate at the same level as wildtype, we modelled the evolution of the viral population over time ( Figure 1B, Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We first attempted to model the evolution of gene drive resistance using numerical simulations. Our initial study indicated that after co-infection with a wildtype and a gene drive viruses, around 5-10% of viruses remained unconverted and had a mutated target site that rendered them resistant to the drive (7). Using a 10% estimate and considering in this scenario that resistant viruses would replicate at the same level as wildtype, we modelled the evolution of the viral population over time ( Figure 1B, Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…We next evaluated experimentally the evolution of resistance in cell culture. Our initial experimental system involved an unmodified hCMV virus expressing GFP (strain Towne, referred hereafter as Towne-GFP) and an mCherry-expressing gene drive virus (GD-UL23) targeting UL23 (7) (Figure 2A). UL23 is dispensable in normal cell culture conditions (8, 9), but the GD-UL23 virus was built in a different viral strain (TB40/E) and replicated significantly slower than Towne-GFP (t-test: p=0.0065, Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations